Debate on Work Ethos in Reflection of The Prophet’s Hadith - Muhammad Alwi; Abdillah; Muhammad Fakri Amir (Sao Literasi Publisher, Yayasan Pendidikan Khaerul Munif, 2022)
This article aims to describe the concept of work ethic in Islam and the Hadith interpretation of work ethic. This article is literature research that adopts analytical descriptive method through reading various literatures. Data obtained from various credible literatures and various other supporting information are then presented with a strong analytical instrument based on the normative basis and interpretation of hadith about work ethic. The results of the study show that in Islamic teachings it is taught about how to work well based on Islamic law. A person who has faith and a strong soul will have a good work ethic spirit, so that at work he will be enthusiastic and earnest to achieve success and prosperity in fulfilling the necessities of life. The value of work ethic related to Hadith is used as a foothold in the spirit of motivation to work. The interpretation of the hadith about the concept of work ethic includes to meet the needs of oneself and one's family, work with one's own hands and prohibit begging, work is a form of worship and work as a form of appreciation for the work itself. While the quality of the hadith related to the work ethic is authentic, both in terms of the Sanad and the meaning. This makes it possible to contextualize the hadith understanding of work ethic.